Związki między wybranymi cechami drzewa a niektórymi właściwościami drewna młodocianego sosny zwyczajnej (Pinus sylvestris L.) - Tomczak, Arkadiusz (Leśne Prace Badawcze, 2014)
The aim of this study was to determine relationships between selected properties of juvenile wood and characteristics of the stem and crown of Scots pine. Analyses were conducted in northern Poland in eight mature pine monocultures. Nine trees were selected in each experimental site and their stems were divided into five sections. The centers of the sections were established at a height of 1.3 m from the tree base and at points corresponding to 20, 40, 60 and 80% tree height. Samples were taken from these locations, and these samples were prepared for analyses of basic density, compressive strength along the grain and static bending, as well as the modulus of elasticity during bending. The mean height of the investigated group of trees was 26.0 m with an average diameter breast high of 33.6 cm. The mean crown depth was 7.8 m and crown diameter was 3.6 m, and the mean basic density (Qu) of juvenile pine wood was 416 kg/m 3 . The average compressive strength along the grain (CS) was determined to be 22.3 MPa, while static bending strength (BS) was 45.8 MPa. The recorded modulus of elasticity (MOE) was 4726 MPa. Both in general terms and when dividing stems into sections, the wood properties correlated with tree characteristics to various degrees. All indexes were negative indicating that trees of greater dimensions produce juvenile wood of inferior quality. Properties of juvenile wood formed during various periods of tree life were mostly related to diameter breast high and crown depth. They were also correlated with tree height, but only to a limited extent. In contrast, properties of wood from the middle stem sections were significantly correlated with crown diameter.